HUBUNGAN ANTARA KONSEP DIRI DAN KEMAMPUAN KOMUNIKASI DENGAN KEMAMPUAN ADAPTASI PEGAWAI BARU DI PERUSAHAAN PERBANKAN - Rahadianto, Anugrah; Noor Rakhmad, wiwid; Hasfi, Nurul (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
New employees often face difficulties in adapting to their new work environment, leading to high turnover rates, especially in the banking sector. These difficulties are influenced by selfconcept and communication skills. This study examines the relationship between self-concept and communication skills with the adaptation ability of new employees in banking companies. The study uses a positivist paradigm and a quantitative approach, involving 100 respondents aged 21-45 years with a maximum working period of one year. A survey method with a questionnaire was used to measure the variables studied. The results of the correlation analysis showed a significant positive relationship between self-concept and adaptation ability, and between communication skills and adaptation ability. This relationship aligns with Henri Tajfel's social identity theory and Giles & Ogay's (2007) social accommodation theory. The results of the coefficient of determination test showed a significant positive relationship between self-concept and communication skills simultaneously with adaptation ability, consistent with what Schneiders stated in Ulfa et al. (2022). The results of this study indicate that new employees with a positive self-concept and good communication skills can adapt quickly and effectively in a strict and high-risk work environment. This shows that a good self-concept and communication skills greatly support the adaptation process of new employees in a new workplace.